Exploring Teacher Experiences of Total Physical Response (TPR) to Teach English Vocabulary in Inclusive Elementary Classroom - Indah Permatasari Harahap; Muhammad Dalimunte (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study aims to explore teachers’ experiences in implementing the Total Physical Response (TPR) method in teaching English vocabulary in inclusive elementary school classrooms. This study employs a qualitative approach using a case study design. The research participant was one English teacher selected through purposive sampling. Data were collected through semi-structured interviews, classroom observations, and documentation, and were analyzed using thematic analysis. The results indicate that the implementation of TPR was adaptive in nature, responding to the diverse needs of students. This method was found to enhance student engagement and participation, particularly through the use of movements that facilitate concrete understanding of vocabulary. However, the implementation of TPR also faced challenges, such as classroom management and differences in student characteristics. To address these issues, the teacher employed strategies such as assigning tasks in stages and adjusting the level of difficulty. This study confirms that the success of TPR in an inclusive context heavily depends on the teacher’s flexibility and role as a learning facilitator.